2013
DOI: 10.1186/1471-2393-13-39
|View full text |Cite
|
Sign up to set email alerts
|

Local health workers’ perceptions of substandard care in the management of obstetric hemorrhage in rural Malawi

Abstract: BackgroundTo identify factors contributing to the high incidence of facility-based obstetric hemorrhage in Thyolo District, Malawi, according to local health workers.MethodsThree focus group discussions among 29 health workers, including nurse-midwives and non-physician clinicians (‘medical assistants’ and ‘clinical officers’).ResultsFactors contributing to facility-based obstetric hemorrhage mentioned by participants were categorized into four major areas: (1) limited availability of basic supplies, (2) lack … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 13 publications
2
22
0
Order By: Relevance
“…However, a policy of vaginal birth after cesarean delivery is justified because cesarean deliveries carry significant additional risks. 152 Our meta-analysis has the advantage of a large number of included patients. 45 Few cases had accessed arterial embolization despite reported high success rates.…”
Section: Discussionmentioning
confidence: 99%
“…However, a policy of vaginal birth after cesarean delivery is justified because cesarean deliveries carry significant additional risks. 152 Our meta-analysis has the advantage of a large number of included patients. 45 Few cases had accessed arterial embolization despite reported high success rates.…”
Section: Discussionmentioning
confidence: 99%
“…In high-income contexts, lack of adequate out-of-hours care (which includes not just staff numbers, but also the skill mix and deployment of those staff) has been shown to leave women and neonates vulnerable [ 39 ]. In the Malawian context, maternal death reviews have highlighted human resources constraints and/or insufficient clinical skills as key factors that delay adequate and timely care [ 15 , 16 , 29 , 40 ]. These factors also have important consequences for health workers.…”
Section: Discussionmentioning
confidence: 99%
“…There is consistent evidence from high-income contexts that nurses value practice environments that ensure enough staff to provide adequate patient care [ 23 ]; a broad consensus on the relationship between job demands (such as workload, time pressure and staffing levels) and burnout, particularly emotional exhaustion [ 24 , 25 ]; and a positive, significant association between high-nurse patient ratios and burnout [ 26 ]. The limited evidence from sub-Saharan Africa shows the negative effect of staffing levels and workload on nursing cadres, predicting outcomes such as burnout [ 27 ], while research in Malawi has indicated that staff perceptions of insufficient staff or time to carry out their work can predict key variables concerning motivation and attrition [ 28 ], as well as resulting in sub-standard care and poor attitudes towards women [ 29 ]. These factors drive a vicious cycle where the lack of an enabling environment leads to poor quality clinical care and disrespect, which in turn dissuade women from facility-based delivery, encourage them to bypass facilities with a bad reputation, or to delay seeking care and then arrive in critical condition [ 16 , 21 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, as the study was facility-based, such cases may have been selectively missed: since postpartum haemorrhage results in sudden, copious amounts of blood loss as well as rapid death, most patients possibly cannot reach a health facility, as most births are in rural areas in Pakistan and similar countries. 26 28 …”
Section: Discussionmentioning
confidence: 99%